Strategi Komunikasi Pemasaran Sip Studio Photography Melalui Media Instagram - Azriel Afdhal Furqani; Siti Nursanti; Fardiah Oktariani Lubis (KOMVERSAL, 2025)
This study aims to determine the marketing communication process carried out by Sip Studio Photography through Instagram media. This study uses the theory of The Circular Model Of Some which includes four main aspects, namely share, optimize, manage, engage which aims to support effective marketing communication strategies carried out by Sip Studio Photography. The method used is a case study with a qualitative approach that is descriptive and the data collection technique uses the results of observations and interviews with several informants such as owners, admins and users of their services as well as observation and documentation. The results of this study indicate that Sip Studio Photography uses new media as a marketing communication strategy in order to adapt to changes experienced by consumers due to the development of information and communication technology.